Exploring the Semantic Meanings of 'نذير' in the Qur'an: Comparative Tafsir Analysis - Burhanudin Al-Ghoni; Eko Sumardianto; Moh Fauzi Rahman Ramdhani; Muhamat mubin (Bulletin of Islamic Research, 2023)
This study examines the semantic meanings of the words نذير (nadhir) and ينذر (yunzir) in the Qur'an, which mean "a warner" and "to warn," derived from the root ن-ذ-ر. The Research Gap lies in the lack of a comprehensive analysis comparing the semantic meanings of these terms through syntagmatic, paradigmatic approaches, and tafsir comparison. The Research Method employs a semantic approach encompassing morphological analysis, the contextual use of these terms in the Qur'an, and a comparative study of two major exegeses: Tafsir As-Sa'di and Shafwatut Tafasir. Data were collected from relevant Qur'anic verses, supported by classical and contemporary tafsir literature and other academic references. The Research Findings reveal that Tafsir As-Sa'di emphasizes Allah’s mercy in the warnings as an act of compassion to save humanity from punishment, while Shafwatut Tafasir by Ash-Shobuni focuses on the aspect of threat as a form of divine justice. The Significance of this study lies in its contribution to expanding the understanding of Qur'anic warnings through in-depth semantic analysis, providing new insights into Islamic preaching (dakwah) and Qur'anic studies.